Analysis the influence of marketing mix and after sales service towards purchase decision on Toyota Yaris at PT. Agung Automall Duri. - Heru Putra Setiawan; Jushermi '; Restu ibrahim (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
This study aimed to analyze the influence of the marketing mix which consisting of Price, Product, Promotion and After sales service towards purchase decision on Toyota Yaris at PT. Agung Automall Duri located on jl.Raya Dumai Km thriteen, number four Duri. The population in this study are the consumers who bought Toyota Yatis car at PT. Agung Automall in year two thousand eleven. The research conducted by using census method with members of thirty seven respondents. Data analyze using multiple linier regression model with SPSS version seventeen.The results of this study showed that simultaneously, all independent variables : Price, Product, Promotion and After sales service have a significant effect towards dependent variable (purchase decision). It can be seen from the calculated F value is greater than the E table. While partially each variable : Price, Product and promotion has a significant effect that indicated from the T value of each variable is greater than. The T table but after sales service variable has not significant effect to its T value is smaller than the T table. The coefficient of determination (Adjusted R2) shows the independent variables contributed very powerfull in explaining the dependent variable (Purchase decision).Keywords: Purchase decision, Price, Product, Promotion, After sales service.